PENINGKATAN KEMAMPUAN MENETAPKAN KKM DENGAN DISKUSI KELOMPOK KECIL BAGI GURU MATEMATIKA SMKN 1, SMKN 4, SMK PGRI 2 KOTA JAMBI - Yendarman Yendarman (Jurnal Ilmiah Universitas Batanghari Jambi, 2016)
The study aims to reveal increase in the ability to determine KKM with small  group discussion for Teachers of mathematics SMKN 1, SMKN 4, SMK PGRI 2 Jambi city. This study tested the hypothesis “by using a small group discussion to improve the ability of teachers in the subjects of mathematics sets of minimal completeness criteria (KKM)”. This research conducted action research in the format of school, this action conducted in two circles such as: action planning, implementation of act, observation, evaluation and reflection. The method used is a small group discussion. The result of research first action that known the teachers ability to set up the mark of KKM improved in pretest 53.8 to 79 or 49% increasing . The result of second action showed the significant mark is average 93% to 94%. This research reveals that hypothesis is accepted. This implies that in order to improve the ability of teacher to set up KKM in SMK by using small discussion is sought. keyword: Small-Group Discussion